2003
DOI: 10.1016/s0014-5793(03)01013-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria from ejaculated human spermatozoa do not synthesize proteins

Abstract: Sperm motility is dependent on mitochondrial ATP production that relies on the coordinated expression of the mitochondrial and nuclear genomes. It is generally accepted that mammalian ejaculated spermatozoa retain the ability to synthesize mtDNA-encoded proteins but not most of the nuclear ones. This implies an asynchronous regulation of the oxidative phosphorylation-related genes encoded by each genome. Trying to investigate this issue, we unexpectedly found that ejaculated human spermatozoa do not synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 21 publications
1
17
0
1
Order By: Relevance
“…The mammalian spermatozoa must be progressively motile for a certain period of time to fertilize an oocyte (Mukai & Okuno, 2004). It has been proposed that the energy required to regulate sperm motility is provided by ATP, which is predominantly produced via mitochondrial respiration (D ıez-S anchez et al, 2003;Miki et al, 2004;Mukai & Okuno, 2004). Therefore, if mitochondrial respiration is unable to synthesize ATP, it could decrease the sperm motility.…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian spermatozoa must be progressively motile for a certain period of time to fertilize an oocyte (Mukai & Okuno, 2004). It has been proposed that the energy required to regulate sperm motility is provided by ATP, which is predominantly produced via mitochondrial respiration (D ıez-S anchez et al, 2003;Miki et al, 2004;Mukai & Okuno, 2004). Therefore, if mitochondrial respiration is unable to synthesize ATP, it could decrease the sperm motility.…”
Section: Discussionmentioning
confidence: 99%
“…Because mature mammalian spermatozoa have stopped protein synthesis (27), this analysis cannot be performed at the mRNA level (e.g. by reverse transcription-PCR or in situ hybridization).…”
Section: Expression Of Hor17-4 Stimulatory G-proteins and Mac(s)-mentioning
confidence: 99%
“…The question, therefore, of whether sperm has a translational capacity that cannot be ascribed to another contaminating cell type (including contaminating bacteria) remains open. De novo, chloramphenicol-(CP-) sensitive, mitochondrially directed protein synthesis in capacitating human sperm was recently demonstrated using the uptake of 35 S-methionine-lysine and BODIPY lysine tRNA [47] This report did not cite a study appearing three years earlier, concluding that protein synthesis in sperm was due to CP-sensitive bacterial contamination (repeating an assertion made almost 40 years previously; [53,54]). The only other report of de novo protein synthesis in sperm used a 2D PAGE based proteomic approach to identify 44 differentially expressed proteins in capacitated versus noncapacitated sperm including sperm capacitated in the presence of chloramphenicol [47].…”
Section: Historical Contextmentioning
confidence: 92%
“…Between them, MacLaughlin and Terner [66] and Premkumar and Bhargava [67] demonstrated that mature bovine spermatozoa have no nuclear transcription to speak of (as might be expected) but that mitochondrial RNA was actively transcribed. Translation of (mitochondrial) RNAs was inferred rather than demonstrated at the time although at least one more recent report suggested that even mitochondrial gene expression is also absent in mature sperm [54].…”
Section: Historical Contextmentioning
confidence: 99%
See 1 more Smart Citation